(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
One of the main causes of mortality in the 21st century has been cancer. Even among cancer, chronic myelogenous leukaemia (CML) is one of the main causes for cancer associated death. Despite its ubiquity the breadth of therapy is restricted by its high cost and lack of effectiveness. Spergulin –A, a saponin which is a triterpenoid, isolated from an n-butanol fraction of the flowering plant Glinus oppositifolius has been reported previously for its anti-leishmanial activity. In this study, Spergulin-A was isolated from Glinus oppositifolius and its Identification and structural confirmation was achieved by NMR, after which it was tested for its anti-CML action. As per the present results, Spergulin-A was found to cause growth inhibition and trigger apoptosis in K562, a cell line of chronic myelogenous leukaemia, origin. Moreover, Spergulin-A has demonstrated no detrimental effects against normal cell lines. Based on these results, it can be reasonably concluded that Spergulin-A may be used as an anti-CML agent.